Evaluasi Kinerja Simpang Empat Bersinyal (Studi Kasus Simpang Magelang dan Selokan Mataram Yogyakarta) - Herdianus Markus; Ani Tjitra Handayani; Herna Puji Astutik (ReTII, 2023)
The flow of vehicle traffic at the Magelang intersection and Mataram ditch in Yogyakarta is very highly influenced by the activities of the community, because it is near the main route entering Yogyakarta City and Sleman Regency. This research aims to determine the performance of existing traffic and alternative handling solutions at this intersection. The data used is primary data obtained from direct surveys in the field which were carried out for three days on Friday 26 May, Sunday 28 May and Monday 29 May 2023. Analysis at intersections was carried out in accordance with the technical requirements for signalized intersections according to MKJI 1997 and modeling was carried out using VISSIM software. . Modeling using VISSIM software on existing conditions and 2 alternative treatments to compare the level of service at the Magelang intersection and Mataram Yogyakarta sewer. The results of this research: The traffic performance of the intersection in the existing condition of the north arm has a capacity of 1358 pcu/hour, the east arm 362 pcu/hour, the south arm 1349 pcu/hour, the west arm 225 pcu/hour. With the degree of saturation of the north arm 0.685, the east arm 0.824, the south arm 0.607, the west arm 0.897. Time delay of MKJI 1997 north arm 38.5 sec/pcu, east arm 78.2 sec/pcu, south arm 36.8 sec/pcu, west arm 82.4 sec/pcu. VISSIM delay time for north arm 22.83 sec/pcu, east arm 50.71 sec/pcu, south arm 16.32 sec/pcu, west arm 70.12 sec/pcu. The length of the 1997 MKJI queue for the north arm was 86 meters, the east arm 78 meters, the south arm 78 meters, the west arm 41 meters. The length of the VISSIM queue for the north arm is 78.39 meters, the east arm is 65.74 meters, the south arm is 72.41 meters, the west arm is 39.94 meters. Meanwhile, the Level of Service for the north arm is D, the east arm is F, the south arm is D, the west arm is F .